Collective Efficacy as a Task Specific Process: Examining the Relationship Between Social Ties, Neighborhood Cohesion and the Capacity to Respond to Violence, Delinquency and Civic Problems. Issue 1 (29th June 2013) - Wickes, Rebecca; Hipp, John R.; Sargeant, Elise; Homel, Ross
Abstract: In the neighborhood effects literature, collective efficacy is viewed as the key explanatory process associated with the spatial distribution of a range of social problems. While many studies usefully focus on the consequences of collective efficacy, in this paper we examine the task specificity of collective efficacy and consider the individual and neighborhood factors that influence residents' perceptions of neighborhood collective efficacy for specific tasks. Utilizing survey and administrative data from 4, 093 residents nested in 148 communities in Australia, we distinguish collective efficacy for particular threats to social order and assess the relative importance of social cohesion and neighborhood social ties to the development of collective efficacy for violence, delinquency and civic/political issues. Our results indicate that a model separating collective efficacy for specific problems from social ties and the more generalized notions of social cohesion is necessary when understanding the regulation potential of neighborhoods.